CRIMINAL LAW RESPONSIBILITY AGAINST NOTARIES AS LAND MAFIA OCCUPATIONS - Irfan Rizky Pradya; Ismaidar (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Land mafia individuals are two or more people working together to seize other people's land or state land. It is not appropriate if only a Notary causes the exchange of original and fake certificates, embezzlement, fraud so that the action fulfills the elements of a legal violation. Using the Normative Juridical Research Method, which is close to legislation (Statue approach) and case approach (Cases approach) that the legal umbrella of Law no. 2 of 2014 regarding amendments to Law Number 30 of 2004 concerning the Position of Notary Public, there are no criminal provisions regulated so that this could potentially occur under the Criminal Code. In the context of Criminal Law Accountability for Notaries for the Deeds they make, as an alternative to provide protection for people who are harmed by Notaries as Land Mafia Persons. The results of this writing are that in the future the Government and the Minister of ATR/BPN (National Land Agency) together will immediately draft a law that provides regulations regarding the Eradication of Land Mafia Persons so that in dealing with Land Mafia Crimes they can be eliminated and carry out strict controls carried out by the Regional Supervisory Council of Notaries and The Central Notary Supervisory Council is to prevent Notaries who abuse negligence in carrying out their official duties so that there is no reproach for land mafia individuals to collaborate with Notaries.